TINJAUAN KUALITAS FISIK, KIMIA DAN MIKROBIOLOGI AIR TAMAN BEJI DESA UBUNG KAJA DENPASAR TAHUN 2018 - Ni Luh Putu Feby Diah Ningsih; made bulda (Poltekkes Kemenkes Denpasar, 2018)
Abstract: North Ubung Village is one area that has 6 (six) water springs. One of them is the Taman Beji water spring located at Jalan Kendedes Denpasar. This water spring is used by local people for drinking water. In this water spring quality checks have been done, but that is not found. The purpose of this research is to know the physical, chemical and microbiological qualities of Taman Beji North Ubung Village Denpasar. The type of research used to descriptive research. The population and samples in this research is Taman Beji water spring North Ubung Village. Data collected in this research are primary and secondary data. The data were collected using laboratory equipment to measure the physical, chemical and microbiological qualities of Taman Bejis water and the eye protection inspection sheet to assess the protection of the Taman Beji water spring. Physical and microbiological measurements were performed twice (2) an chemical measurement was performed only one (1) time. Based on the results obtained that the physical parameter of Taman Bejis water with temperature 280C dan 290C, the same turbidity results in two measurements of 0,11 NTU, chemical parameter that Ph 7 and hardness 60 mg/l, microbiological parameter of Taman Bejis water measured as much twice with results is Eschericia coli 0/100 ml sample and Total Coliform Bacteria 0/100 ml sample. So that the water of Taman Beji is qualify of Permenkes No. 492/MENKES/PER/IV/2010 about Water Quality Requirement. It is recommended for the community and village apparatus to fix PMA Taman Beji to avoid pollution and not to cause water borne disease if the water is consumed by the community.Keywords : Physical Quality; Chemistry and Water Microbiology